2021
DOI: 10.1108/wje-03-2021-0146
|View full text |Cite
|
Sign up to set email alerts
|

Shielded metal arc welding of AISI 409M ferritic stainless steel: study on mechanical, intergranular corrosion properties and microstructure analysis

Abstract: Purpose The purpose of this study is on AISI 409 M ferritic stainless steel (FSS) which is developing a preferred choice for railway carriages, storage tanks and reactors in chemical plants. The intergranular corrosion behavior of welded SS 409 M has been studied in H2SO4 solution (0.5 M) with the addition of NH4SCN (0.01 M) with different heat input. As this study is very important in context of various chemical and petrochemical industries. Design/methodology/approach The microstructure, mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The propensity for the occurrence of intergranular corrosion increased with heat input. [38] 409M FSS SMAW -DL-EPR H2SO4 (0.5 M) with the addition of NH4SCN (0.01 M)…”
Section: Utilized Welding Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The propensity for the occurrence of intergranular corrosion increased with heat input. [38] 409M FSS SMAW -DL-EPR H2SO4 (0.5 M) with the addition of NH4SCN (0.01 M)…”
Section: Utilized Welding Methodsmentioning
confidence: 99%
“…The intergranular corrosion attack on FSS (AISI 430) weldments were aggravated by the Cu-CuSO 4 with 50 % H 2 SO 4 corrosive solution [37]. Ambade et al [38] studied the influence of welding heat input on the corrosion behaviour of 409M FSS weldment. It is observed that the width of HAZ increased with heat input.…”
Section: Utilized Welding Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different types of corrosion and different factors such as metal type, corrosive environment, different welding processes, which affect the corrosion of metals and their alloys. Many studies have been done in this field (Ambade, et al , 2021; Tembhurkar et al , 2021; Ambade et al , 2021).…”
Section: Introductionmentioning
confidence: 99%